Olive Leaves Extract Encapsulated by Spray-Drying in Vacuum Fried Starch–Gluten Doughs - Gimenez-Castillo, B (Institution of Chemical Engineers, 2017)
Olive leaves extract (OLE) was microencapsulated with inulin (OLE-IN) by spray-drying using a central composite design. Oleuropein encapsulation efficiency and recovery values were over 87% in the OLE-IN microparticles obtained under optimal conditions. OLE or OLE microparticles were added into starch–gluten fried matrices with the aim of studying the effect of microencapsulation and the frying method on the polyphenols content and antioxidant activity, fat content and crispness. Vacuum starch–gluten fried samples absorbed slightly, but significantly, less oil than the atmospheric fried ones (except for the dough with 350 mg GAE/kg), but crispness was higher in the atmospheric fried products. Although vacuum fried matrices showed significantly higher content of polyphenols than atmospheric fried matrices, both types of matrices showed similar antioxidant activity, suggesting the formation of antioxidant metabolites derived from the Maillard reaction during the atmospheric frying. The results highlighted the importance of the microencapsulation of OLE to preserve the beneficial effects of polyphenols in processed food. © 2017